(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
A relatively new shoreline section on Peace Reach, Williston Lake, north-eastern British Columbia, provides continuous exposure through a Triassic-Jurassic boundary succession, with apparent stratigraphic continuity from the Pardonet Formation (Upper Norian) into the overlying Fernie Formation (Hettangian and younger). These rocks are part of autochthonous North America, deposited along the western margin of the Jurassic craton. The section at Black Bear Ridge consists of 22 m of flaggy-bedded, brown-weathering siltstones and several thick, resistant siltstones, and contains calcareous concretions which have yielded most of the three-dimensional ammonites. While it is clear these ammonites represent parts of the lower, middle and upper Hettangian, the sequence of faunas differs somewhat from those reported from the Queen Charlotte Islands and Nevada. This is the first record of an extensive sequence of Hettangian strata and ammonite faunas in the Fernie Formation. Lower Hettangian faunas include poorly preserved, laterally flattened Psiloceras (P. majus, P. plicatum, P. cf. rectocostatum, P. cf. planocostatum), occurring throughout the lower part of the section from 3.0 to 8.3 m. At 9.5 m Waehneroceras appears, representing the middle Hettangian, followed by Sunrisites sunrisense at 10.8 m, and the first Schlotheimia at 13.3 m. A single large specimen of Alsatites liasicus is associated with these faunas. Beds above 13.3 m yield several species of Schlotheimia (S. angulata, S. angulata densicostata, S. cf. oxygonia), Kammerkarites frigga and Laqueoceras sp., indicating the lower parts of the upper Hettangian. Uppermost Hettangian faunas occur at the top of the exposed section in beds from 21.0 to 21.7 m, and include Badouxia (B. canadensis, B. striata, B. oregonensis) and Pseudaetomoceras doetzkirchneri.